2003
DOI: 10.1110/ps.0233703
|View full text |Cite
|
Sign up to set email alerts
|

The likelihood of aggregation during protein renaturation can be assessed using the second virial coefficient

Abstract: Protein aggregation is commonly observed during protein refolding. To better understand this phenomenon, the intermolecular interactions experienced by a protein during unfolding and refolding are inferred from second virial coefficient (SVC) measurements. It is accepted that a negative SVC is indicative of proteinprotein interactions that are attractive, whereas a positive SVC indicates net repulsive interactions. Lysozyme denatured and reduced in guanidinium hydrochloride exhibited a decreasing SVC as the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 30 publications
3
84
0
5
Order By: Relevance
“…Como o estado D tem maior exposição de sítios para ligação de uréia que o estado N 47 , a hidratação da proteína mediada pela uréia deve ser maior no estado D que no estado N, de tal forma que o estado D deve ser favorecido pela uréia. O hidrocloreto de guanidina também forma ligações de hidrogênio com grupos das cadeias laterais dos aminoácidos e das ligações peptídicas 48,49 , que também estão mais acessíveis ao caotrópico no estado desnaturado.…”
Section: Equilíbrio De Estabilização De Proteínas Em Soluções Aquosasunclassified
“…Como o estado D tem maior exposição de sítios para ligação de uréia que o estado N 47 , a hidratação da proteína mediada pela uréia deve ser maior no estado D que no estado N, de tal forma que o estado D deve ser favorecido pela uréia. O hidrocloreto de guanidina também forma ligações de hidrogênio com grupos das cadeias laterais dos aminoácidos e das ligações peptídicas 48,49 , que também estão mais acessíveis ao caotrópico no estado desnaturado.…”
Section: Equilíbrio De Estabilização De Proteínas Em Soluções Aquosasunclassified
“…When the negative B 22 value further decreases, solution conditions are obtained enhancing particle-particle attractions, and as a result in a number of cases amorphous protein precipitation is observed [51][52][53].…”
mentioning
confidence: 99%
“…L-Arg is known to be able to prevent aggregation caused by hydrophobic interactions (Tsumoto et al 2004), by masking hydrophobic regions and reducing attractive intermolecular interactions (Ho et al 2003). In silico modelling has shown that the guanidium group of L-Arg interacts with hydrophobic patches of protein while the polar carboxyl part of L-Arg forms a hydrophilic layer (Li et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Tag removal from IT1 VP1, containing a hydrophobic epitope, results in only free GST and aggregated IT1 VP1. acids (Ho et al 2003;Leibly et al 2012;Tsumoto et al 2004), osmolytes (Leibly et al 2012), and molecular chaperones (Lanckriet and Middelberg 2004;Prashar et al 2011;Serno et al 2011) as detailed in Table 3.2. Thrombin activity in the different buffer conditions was assessed and confirmed that complete digestion of the GST-VP1 fusion was achieved between pH 7.0 and pH 9.0, irrespective of the additive present.…”
Section: High-throughput Buffer Screenmentioning
confidence: 99%